Cause Analysis and Process Improvement Measures of Primary Forging Cracking for 20 t Flat Ingot of N08120 Nickel-based Corrosion-resistant Alloy - Liu Yu, Xu Wenliang (Teshugang)
With regard to the forging cracking problem of 20 t flat ingot of N08120 nickel-based corrosion-resistant alloy， experiments and on-site process analysis were carried out. The solidification structure near the crack and crack surface composition were explored by macrostructure inspection， optical microscope and scanning electron microscope， combined with the equilibrium phase diagram and on-site data of the material ， the comprehensive analysis showed that the cracking was caused by the internal solidification defects of the ingot and improper heating process before forging. During the solidification process， it was prone to form porosity and shrinkage defects in the lower middle part of the flat ingot， and there was a stacked charging mode of cold ingots during heating， resulting large tensile stress inside the ingot. When the stress value was higher than the internal bonding strength， cracks would initiate and expand outward during forging process. By reducing the casting speed of shrink head to 30% of that of ingot body， adding the heating agent in advance when the molten steel level reached 2/3 of height of the shrink head， increasing heating agent from 2 kg/t to 2.5 kg/t and adding carbonized rice husk in order to improve the insulation effect， increasing the proportion of hot-feeding ingots in the forging process and strictly prohibiting the stacking of cold ingots into the furnace， the problem of forging cracking was solved.